PERAN FINTECH PEER-TO-PEER LENDING DALAM PENGEMBANGAN UMKM DI INDONESIA: STUDI LITERATUR - Lusi Dewiyanti; Siti Yuniati Robiah; Istia Wardhani Nur Ramadhanty Putri; Salsa Wulan sari (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. Abstract – Micro, Small, and Medium Enterprises (MSMEs) play a crucial role as a pillar of national economic stability. However, limited access to formal financing due to unbankable status remains a classic structural barrier. This study aims to explore in depth the role of Financial Technology Peer-to-Peer (P2P) Lending in overcoming the credit gap and supporting the development of MSMEs in Indonesia. The research method used is a qualitative approach with a literature study (library research) technique through the collection and analysis of academic texts and relevant regulatory documentation. The results show that P2P Lending platforms effectively solve capital bottlenecks through collateral-free lending mechanisms by relying on Alternative Credit Scoring (ACS) based on users' digital footprints. The dimension of this strengthening is accelerated through the adoption of Sharia principles (murabahah, mudharabah, musyarakah contracts) which provide psychological safety, as well as institutional strategic partnership schemes (channeling) between banks and fintech that extend the financing reach to remote areas. Nevertheless, the utilization of this digital financing carries financial risk consequences in the form of high service fees or daily interest burdens as well as cybersecurity threats that demand an increase in business actors' financial literacy. This study concludes that all literature agrees in supporting the positive role of fintech P2P lending, provided that it is balanced by strict regulatory oversight from the Financial Services Authority (OJK) and the enforcement of juridical boundaries for platform managers to maintain the sustainability of community economic stability. Keywords: Financial Technology, P2P Lending, MSMEs, Access to Capital, Literature Study Abstrak – Abstrak Sektor Usaha Mikro, Kecil, dan Menengah (UMKM) memegang peranan krusial sebagai pilar stabilitas ekonomi nasional. Namun, keterbatasan akses terhadap pembiayaan formal akibat status unbankable menjadi hambatan struktural yang klasik. Penelitian ini bertujuan untuk mengeksplorasi secara mendalam peran Financial Technology Peer-to-Peer (P2P) Lending dalam mengatasi kesenjangan permodalan (credit gap) serta mendukung pengembangan UMKM di Indonesia. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik studi literatur (library research) melalui pengumpulan dan analisis dokumentasi teks akademik serta regulasi terkait. Hasil penelitian menunjukkan bahwa platform P2P Lending efektif memecahkan kebuntuan modal melalui mekanisme pinjaman tanpa agunan (collateral-free Lending) dengan mengandalkan Alternative Credit Scoring (ACS) berbasis jejak digital pengguna. Dimensi penguatan ini mengalami akselerasi melalui adopsi prinsip syariah (akad murabahah, mudharabah, musyarakah) yang memberikan rasa aman psikologis, serta skema kemitraan strategis kelembagaan (channeling) antara bank dan Fintech yang memperluas jangkauan pembiayaan hingga ke pelosok daerah. Kendati demikian, pemanfaatan pembiayaan digital ini membawa konsekuensi risiko finansial berupa tingginya beban biaya layanan atau bunga harian serta ancaman keamanan siber yang menuntut adanya peningkatan literasi keuangan pelaku usaha. Penelitian ini menyimpulkan bahwa seluruh literatur sepakat mendukung peran positif Fintech P2P Lending, asalkan diimbangi oleh pengawasan regulasi yang ketat dari Otoritas Jasa Keuangan (OJK) serta penegasan batasan yuridis bagi pengelola platform demi menjaga keberlanjutan stabilitas ekonomi kerakyatan. Kata Kunci: Financial Technology, P2P Lending, UMKM, Akses Permodalan, Studi Literatur.